2003
DOI: 10.1590/s1676-24442003000100007
|View full text |Cite
|
Sign up to set email alerts
|

Köln's unstable hemoglobin: case report and literature review

Abstract: Unstable hemoglobins are a group of genetic variants of hemoglobins caused by the mutation of amino acids into alpha and beta globins and, depending on the points and types of mutation, the result can vary from no clinical symptomatology to severe hemolytic anemia. On the present report, we study the case of a female patient who showed a very exuberant hematological picture for the red series, which suggests hemoglobinic changes; this was confirmed following the conduction of the protocol established by Labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Due to the loss of the hydrogen bond with the 26th residue, the side chain of His117 β flips and its NE2 atom now interacts with another water molecule (not shown in the figure). Previous studies on hemoglobin instabilities suggest that HbE can be unstable when subjected to an increase in temperature ( , ). Our structural studies show that, although there is no direct hydrogen bond between helices B and G near the mutation site of HbE (Figure b), the intersubunit contacts remain the same as those of HbA, presumably due to the presence of the water network that partially connects helices B and G. Among these water molecules, only W2 and W3 are buried, while the other members of this network are on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the loss of the hydrogen bond with the 26th residue, the side chain of His117 β flips and its NE2 atom now interacts with another water molecule (not shown in the figure). Previous studies on hemoglobin instabilities suggest that HbE can be unstable when subjected to an increase in temperature ( , ). Our structural studies show that, although there is no direct hydrogen bond between helices B and G near the mutation site of HbE (Figure b), the intersubunit contacts remain the same as those of HbA, presumably due to the presence of the water network that partially connects helices B and G. Among these water molecules, only W2 and W3 are buried, while the other members of this network are on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal denaturation experiments performed on blood from E/β-thalassemics in the temperature range of 39-41 °C showed the instability of HbE, a finding that was also observed in homozygous HbE (14). Pscheidt et al (15) also showed the instability of HbE by performing a heat test at 50-60 °C, and they suggested that, in particular, any change that reduces the contacts between the subunits that compose the hemoglobin would generate its instability.…”
mentioning
confidence: 93%
“…Unstable hemoglobins are a group of genetic variants of hemoglobins in which the mutation of amino acids into alpha and beta globins affect the structure of the molecule, making it unstable. Some hemoglobins are discreetly unstable and are not associated with clinical symptoms, while other unstable hemoglobins precipitate with great intensity, causing hemolytic anemia, excretion of "free heme" such as dipyrroles, making the patient's urine dark 4 . Kӧln haemoglobin was first described by Pribilla et al in 1965, where they found a "new" haemoglobin in haemoglobin electrophoresis, forming a small band between HbA and HbA2, constituting around 5% of total haemoglobin.…”
Section: Discussionmentioning
confidence: 99%
“…1 Patients with Hgb Köln typically have reticulocytosis, splenomegaly, bilirubin, jaundice, and prolonged dark urine excretion in addition to moderate hemolytic anemia. 2 Prolonged thrombocytopenia or priapism were also reported in certain cases. 3,4 Hemoglobin Köln reports are more common among several regions of the Orient, and throughout Europe.…”
Section: Introductionmentioning
confidence: 99%